Stem-cell therapy for neurologic diseases - Sharma, Shilpa; Gupta, Devendra K. (Journal of Neuroanaesthesiology and Critical Care, 2015)
With the advent of research on stem cell therapy for various diseases, an important need was felt in the field of neurological diseases. While congenital lesion may not be amenable to stem cell therapy completely, there is a scope of partial improvement in the lesions and halt in further progression. Neuro degenerative lesions like Parkinson's disease, multiple sclerosis and amyotrophic lateral sclerosis have shown improvement with stem cell therapy. This article reviews the available literature and summarizes the current evidence in the various neurologic diseases amenable to stem cell therapy, the plausible mechanism of action, ethical concerns with insights into the future of stem cell therapy.
Keywords: Neurologic diseases; stem cells; treatment modalities